HUMAN RIGHTS AS INTEGRAL PART OF THE STATE INTERESTS IN THE POSTBIPOLAR SYSTEM OF INTERNATIONAL RELATIONS - Гарбар, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article considers the role of human rights as an integral part of state’s interests at thecontemporary stage of international relations. The negative tendencies of basic human rights’violations are analyzed in connection with their impact on a state’s political system. The authorargues that human rights enforcement is an integral part of national interests which are of astrategic importance for a state stable development under conditions of globalizations and liberalideas widespread.